PENGARUH LEVEL PEMBERIAN â€œPUYER HERBALâ€ TERHADAP BOBOT HIDUP, KARKAS, GIBLET DAN LEMAK ABDOMEN PADA AYAM BROILER - Bebhe, Gabriela; Sumarno, Sumarno; Fitasari, Eka (Fakultas Pertanian, 2017)
The purpose of this study was to determine the best dosage of puyer herbal in variable addition of herb powder which consists of kencur flour, turmeric powder and wild ginger flour against live weight, carcass, giblet and abdominal fat. The material used is 80 broiler chickens purchased from PT. Panca Patriot Prima kept in postal cage. The feed used is BR1 for 1-7 days old and feeding age 8-35 days formulation consisting of yellow corn, pollard, meat meal, soybean meal, salt, Dl-methionine and lysin. The research treatment P0: feed formulation without puyer herbal, P1: feed formulation + 0.3% puyer herbal, P2: feed formulation + puyer herbal 0.6%., P3 feed formulation + puyer herbal 0.9%. Provision of puyer herbal based on weekly body weight. The research method was Rancangan Randomized Design (RAL) with 4 treatments and 4 replications. The variables studied were live weight, carcass, giblet and abdominal fat. The results showed that the provision of puyer herbal with different levels did not have a significant effect (P>0.05) on live weight, giblet weight and abdominal fat weight in broiler. The weight of carcass had a very significant effect (P0,05) terhadap bobot hidup, bobot giblet dan bobot lemak abdomen pada ayam broiler. Bobot karkas berpengaruh yang sangat nyata (P